A Fábrica da Pólvora de Barcarena e as “Ferrarias del Rey”: um projecto de arqueologia industrial em construção - Cardoso, João Luís (2021)
A synthesis of the research until now carried out at the remarkable cultural space Barcarena Gunpowder Factory is presented, from the time of the founding of the Ferrarias, in the time of D. João II (1487), until the definitive closure of the gunpowder complex, at the end of the 20th century (1988), five hundred years after.